Actividades de Control de las Cuentas Por Cobrar en la Industrial Fideera Rodolfo Pazmiño - Rosero Vera, Rosmary Patricia (2019)
The present research work has as its theme "Control Activities of the Accounts Receivable in the Industrial Fideera Rodolfo Pazmiño of the City of Babahoyo", focuses on analyzing the loans granted and the recovery of the portfolio, with the purpose of maintaining a liquidity through the proceeds from collections of the credit portfolio to customers. The loans granted to clients, cash sales and wholesale and / or retail credit for human consumption noodles, we frame the types of commercial businesses that generate through sales, generally the companies that grant credits, run the uncollectibility risk, late and inopportune payments, with subsequent dates, giving rise to the growth of accounts receivable to customers and undoubtedly making notes the lack of liquidity. He